2016
DOI: 10.1038/srep19279
|View full text |Cite
|
Sign up to set email alerts
|

Geographic origin and evolutionary history of China’s two predominant HIV-1 circulating recombinant forms, CRF07_BC and CRF08_BC

Abstract: To determine the origin and evolutionary history of two predominant and closely-related circulating recombinant forms (CRF07_BC and CRF08_BC), recombinant structures and phylogenies of 7 unique recombinant forms comprised of subtypes of B’ (Thai B linage) and C (designated URFs_BC) from archival specimens of injection drug users (IDUs) collected in 1996 to 1998 from western Yunnan and 4 circulating recombinant forms with B’/C recombinants recently identified (designated nCRFs_BC) in China were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 31 publications
6
56
0
Order By: Relevance
“…As a result, various subtype B'/C recombinants emerged among PWIDs thereafter [30], including the two predominant circulating genotypes believed to be originating from Western Yunnan [31], CRF07_BC [32] and CRF08_BC [33]. In the present study, we reported the first identification of CRF07_BC in a recently-infected blood donor, probably as a result of sporadic introduction of CRF07_BC lineage into the country.…”
Section: Discussionmentioning
confidence: 62%
“…As a result, various subtype B'/C recombinants emerged among PWIDs thereafter [30], including the two predominant circulating genotypes believed to be originating from Western Yunnan [31], CRF07_BC [32] and CRF08_BC [33]. In the present study, we reported the first identification of CRF07_BC in a recently-infected blood donor, probably as a result of sporadic introduction of CRF07_BC lineage into the country.…”
Section: Discussionmentioning
confidence: 62%
“…In some instances, recombination following dual/superinfections can rescue lethally mutated genomes generated from the high mutation rate [6-8] or can result in rapid host adaptation, escape from the elicited immune responses, and/or facilitate resistance to antiretroviral drugs consequently leading to faster disease progression in infected individuals [4]. Thus, intersubtype recombination is a major driving force for HIV evolution and is changing the global epidemiology of HIV-1 with circulating recombinant forms (CRFs) dominating regional epidemics and a number of unique recombinant forms (URFs) reported each year [9-18]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous molecular epidemiology studies from our laboratory1617 and other researchers18 suggested that subtype B’ from Thailand and subtype C from India mixed in southwestern China-Yunan to form the 07_BC recombinant circulating subtype (CRF07_BC) and spread to Sichuan and Xinjiang of Western China by the drug trafficking route1617. Initially, CRF07_BC mainly circulated in the intravenous drug users (IDUs) population of Western China and was further transmitted to Taiwan, Marco, and Japan, which made CRF07_BC become the main subtype in eastern Asia19.…”
mentioning
confidence: 99%
“…CRF07_BC was also called China C since it has the subtype C characteristics in the envelope protein portion202122. The studies as mentioned above from mainland China16172122 together with multiple geographically-derived studies1923 demonstrated the CRF07_BC likely originated from a common ancestor (a single or few founder virus) virus since the sequences could form a unique, homogeneous monophyletic cluster in the phylogenetic tree. The latest large-scale molecular epidemiology survey24 indicates HIV-1 CRF07_BC has become the dominant circulating strain for the IDU population in China and other countries in East Asia.…”
mentioning
confidence: 99%